Welfare and Economic Development During the Health Crisis and Corporate Social Responsibility Disclosure: Evidence Indonesian Manufacturing Companies - Sri Anugrah Natalina; Arif Zunaidi (AKRUAL: JURNAL AKUNTANSI, 2025)
Introduction/Main Objectives: This study tries to show whether public ownership, profitability, net sales and CSR disclosure have or do not have an impact on economic welfare. This research focuses on manufacturing companies because many companies produce products needed by the community. Background Problems: In times of health crisis, the community's economic welfare will increase if the company provides CSR. The amount of corporate CSR disclosure is determined by the support of public ownership, profit levels, and net sales of the company. Novelty: Economic welfare during the health crisis requires further research related to the implementation of CSR in manufacturing companies. Research Methods: This research is quantitative, with the adaptation of exploratory research developed through empirical research. The sampling design in this study used the list of companies on the Kompas 100 index list for two consecutive years, namely 2020 and 2021, which is the period of the start of the health crisis in Indonesia. Finding/Results: This study shows that public ownership and profitability directly and significantly correlate with CSR disclosures. Meanwhile, the Net Sales Index is not significant to CSR disclosures. The variables public ownership, profitability, and index net sales are not significant to the welfare economy. Relationships public ownership, profitability, and index net sales total 48%, CSR disclosure, or R: 0.480, and R-square of 0.23, or 23%. Relationships public ownership, profitability, and index net sales total 14 percent, or R: 0.142, and a coefficient of determination (R-square) of 0.02 or 2%. Conclusion: These results support N. Smith, and T. Smith, that the effectiveness of CSR occurs because of the strategy in its implementation, the CSR strategy must have the support of company ownership and be profitable. These results, when combined with the adaptation of CSR in Indonesia, show that many CSR programs are directed at economic, social, and health patterns.